2008
DOI: 10.1158/0008-5472.can-07-5766
|View full text |Cite
|
Sign up to set email alerts
|

Allelic Imbalance at rs6983267 Suggests Selection of the Risk Allele in Somatic Colorectal Tumor Evolution

Abstract: A common single nucleotide polymorphism (SNP), rs6983267, at 8q24.21 has recently been shown to associate with colorectal cancer (CRC). Three independent SNP association studies showed that rs6983267 contributes to CRC with odds ratios (OR) of 1.17 to 1.22. Here, we genotyped a populationbased series of 1,042 patients with CRC and 1,012 healthy controls for rs6983267 and determined the contribution of SNP to CRC in Finland, using germ line DNA, as well as the respective cancer DNA in heterozygous patients. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
65
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 19 publications
7
65
1
1
Order By: Relevance
“…And although rs16892766 (8q23.3) is significantly associated with an increased CRC risk in MMR mutation carriers (20), its role in MMR-deficient tumors with a sporadic nature seems reduced. Several associations between the risk loci and clinicopathologic parameters have previously been described, including associations between rectal cancer and 11q23.1 and 18q21.1, between early disease onset and both 8q24.21 and 8q23.3, and between MSS tumors and 8q24.21 (8,13,18,19). However, we were unable to replicate any of these associations in our cohort.…”
Section: Resultscontrasting
confidence: 53%
See 1 more Smart Citation
“…And although rs16892766 (8q23.3) is significantly associated with an increased CRC risk in MMR mutation carriers (20), its role in MMR-deficient tumors with a sporadic nature seems reduced. Several associations between the risk loci and clinicopathologic parameters have previously been described, including associations between rectal cancer and 11q23.1 and 18q21.1, between early disease onset and both 8q24.21 and 8q23.3, and between MSS tumors and 8q24.21 (8,13,18,19). However, we were unable to replicate any of these associations in our cohort.…”
Section: Resultscontrasting
confidence: 53%
“…18). Finally, Tuupanen et al (19) identified a tendency for association of rs6983267 (8q24.21) with microsatellite stable (MSS) cancer and a family history of extracolonic cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, we noticed that in B10% cases of the NCT cohort, TEKT4 variations occurred in post-NCT tumour tissues and paired blood DNA but not in pre-NCT tumour tissues. This finding might be explained by LOH 35,36 or an allelic imbalance 37,38 during tumorigenesis as well as tumour development. We propose that WT homozygous tumour cells have an advantage in cell growth and formed the majority of the tumour.…”
Section: Discussionmentioning
confidence: 99%
“…Several chromosomal regions of interest have been identified, including loci for prostate cancer on chromosomes 2, 3,6,7,8,10,11,17,19, and X; for colorectal cancer on chromosomes 8, 10, 11, 15, and 18; and for breast cancer on chromosomes 5,6,8,10, and 16 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). For most of these loci, the effects of the risk alleles seem to be site specific (i.e., different loci were associated with different cancers).…”
Section: Introductionmentioning
confidence: 99%
“…However, one region at 8q24, recognized by the marker rs6983267, was associated with both prostate and colon cancer (6)(7)(8)(9)(10)(11)(12)(13). A modest association [odds ratio (OR), 1.2; 95% confidence interval (CI), 1.0-1.43] of rs6983267 was reported in colorectal cancer patients with a positive family history of any malignancy (14), suggesting the possible involvement of the marker in multisite cancer susceptibility. To better characterize the range of cancers associated with the rs6983267 marker on chromosome 8q24, we genotyped 7,665 cases of cancer and 1,910 controls in the Polish population.…”
Section: Introductionmentioning
confidence: 99%